2017
DOI: 10.1084/jem.20161621
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Ly6Ghigh mature and Ly6Gint immature neutrophils contribute to eradication of S. pneumoniae

Abstract: The spleen is integral for protection against encapsulated bacteria. Using intravital imaging, Deniset et al. demonstrate that resident neutrophil and macrophage populations in the spleen coordinate the rapid clearance of Streptococcus pneumoniae, ensuring sufficient time for subseqent protective antibody production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
232
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(260 citation statements)
references
References 39 publications
21
232
0
1
Order By: Relevance
“…Perhaps neutrophils in rhesus macaques reach full maturation at another anatomical site. Several studies have provided evidence for this to occur in mice (34, 35). …”
Section: Resultsmentioning
confidence: 98%
“…Perhaps neutrophils in rhesus macaques reach full maturation at another anatomical site. Several studies have provided evidence for this to occur in mice (34, 35). …”
Section: Resultsmentioning
confidence: 98%
“…31 Neutrophil depletion was confirmed by flow cytometry in both the peritoneal lavage fluid and spleen of treated mice ( Figure 6B,C,E). To achieve this, we specifically depleted neutrophils in vivo using the well-established anti-Ly6G neutralization antibody or IgG2a isotype control prior to induction of endometriosis.…”
Section: Neutrophil Depletion Alters Local and Systemic Cytokinesmentioning
confidence: 81%
“…They found that, during a systemic Streptococcus pneumoniae infection, most of the bacteria bypass the marginal zone macrophages and are caught by the red pulp macrophages. Mature Ly6G‐high neutrophils residing in the red pulp (that were observed to scan the tissue under basal conditions) were seen plucking the bacteria off the surface of the red pulp macrophages . A dramatic increase in neutrophils was also observed in the marginal zone by 24 h after infection, and interestingly, IVM showed that these neutrophils were grabbed right out of the bloodstream by the marginal zone macrophages.…”
Section: Systemic Infectionsmentioning
confidence: 97%
“…In a more recent study, Deniset et al . used IVM to investigate the coordinated response of splenic neutrophils, macrophages, and B cells to fight Streptococcus pneumoniae .…”
Section: Systemic Infectionsmentioning
confidence: 99%
See 1 more Smart Citation